2020
DOI: 10.3390/microorganisms8040601
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pleurotus ostreatus Laccase Gene in Pichia pastoris and Its Degradation of Corn Stover Lignin

Abstract: Pleurotus ostreatus is a species of white-rot fungi that effectively degrades lignin. In this study, we aimed to efficiently express the lac-2 gene of Pleurotus ostreatus in the Pichia pastoris X33 yeast strain. The enzymatic properties of recombinant yeast were determined, and its ability to degrade corn stover lignin was determined. The results showed the optimum pH values of recombinant laccase for 2,2'-Azinobis-3-ethylbenzothiazoline-6-sulfonic acid, 2,6-dimethoxyphenol, and 2-methoxyphenol were 3.0, 3.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 37 publications
(39 reference statements)
0
8
0
2
Order By: Relevance
“…In another study on sugar cane bagasse and straw, the LC from Pycnoporus cinnabarinus in the presence of HBT caused a noticeable delignification, which correlates with a substantial improvement of saccharification yields. Recombinant LC from Pleurotus ostreatus was shown to be able to degrade corn stover lignin in the presence of suitable mediators . Also a bacterial LC from Bacillus ligniniphilus , alone or in the presence of mediators such as ABTS, has proven effective in lignin (alkaline lignin and milled wood lignin) oxidative degradation, as it has been recently shown.…”
Section: Delignification Main Strategies and Protocolsmentioning
confidence: 88%
See 1 more Smart Citation
“…In another study on sugar cane bagasse and straw, the LC from Pycnoporus cinnabarinus in the presence of HBT caused a noticeable delignification, which correlates with a substantial improvement of saccharification yields. Recombinant LC from Pleurotus ostreatus was shown to be able to degrade corn stover lignin in the presence of suitable mediators . Also a bacterial LC from Bacillus ligniniphilus , alone or in the presence of mediators such as ABTS, has proven effective in lignin (alkaline lignin and milled wood lignin) oxidative degradation, as it has been recently shown.…”
Section: Delignification Main Strategies and Protocolsmentioning
confidence: 88%
“…Recombinant LC from Pleurotus ostreatus was shown to be able to degrade corn stover lignin in the presence of suitable mediators. 156 Also a bacterial LC from Bacillus ligniniphilus, alone or in the presence of mediators such as ABTS, has proven effective 157 in lignin (alkaline lignin and milled wood lignin) oxidative degradation, as it has been recently shown. In particular, a selective removal of S units, within the frame of general demethoxylation, was observed.…”
Section: Protocolsmentioning
confidence: 97%
“…Laccases contain four copper ions except for the laccase that is obtained from Phlebia radiata, which has only two copper ions [245]. There are three types of Lac depending on the copper number at the active site [246]. Type I: copper does not bind O 2 but functions only as an electron transfer site.…”
Section: Lignin Degradation Enzymesmentioning
confidence: 99%
“…Most of the studies on Lac have reported that the fungi and mushrooms present in basidiomycetes, deuteromycetes and ascomycetes act as Lac producers [247]. Among these fungi, the major Lac producers are white-rot fungi in basidiomycetes [246]. White-rot fungi Pycnoporus cinnabarinus, Phlebia radiate, P. ostreatus, and T. versicolour are also known to produce one isoform of Lac [248].…”
Section: Lignin Degradation Enzymesmentioning
confidence: 99%
“…48424 LAC48424-1 P. pastoris [ 164 ] Basidiomycota T. versicolor LCC1 g.e Yarrowia lipolytica [ 165 ] Basidiomycota T. versicolor LCCA, LCCB, P. pastoris [ 166 , 167 ] Basidiomycota Trametes sp. 5930 LAC5930-1 P. pastoris [ 168 ] Basidiomycota T. versicolor Lac6c S. cerevisiae EBY100 [ 169 ] Basidiomycota Lenzites gibbosa LAC P. pastoris [ 164 ] Basidiomycota Pleurotus ostreatus POXA1b g.e S. cerevisiae [ 169 ] Basidiomycota P. pulmonarius (PpuLcc) PpuLcc P. pastoris GS115 [ 170 ] Basidiomycota Pycnoporus sanguineus LCC1 P. pastoris [ 171 ] Basidiomycota P. ostreatus Lac-2 P. pastoris X33 [ …”
Section: Synthetic Biology In Fungo : Gene Editingmentioning
confidence: 99%